2017
DOI: 10.1590/1806-9061-2016-0384
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on the Geometrical and Mechanical Properties of Goose Eggshells

Abstract: This paper examined the properties of goose eggshells to determine possible areas of improvement in egg transport and storage. First, we measured goose egg sizes and performed statistical tests, and found that the major axis, minor axis, and egg-shape index presented normal distribution. Eggshell thickness first increased and then decreased from the blunt end to the sharp end. Second, the shape of individual goose eggshell was measured using a 3D scanner. Volume equation, surface equation, and contour function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 11 publications
2
4
1
Order By: Relevance
“…Shape index ratio determined in the present study was similar to the values (64.9% and 67.5%) reported by Mazanowski and Bernacki [19] for White Italian × Slovakian × Graylag geese and those (66.40% and 67.28%) stated by Arslan and Saatci [20] for geese native to the region of Kars. However, Zhang et al [21] found that the shape index was 69% for 2-year-old geese, which was lower than the value found in the present study. This may be associated with breed, origin, and age of the geese and mainly the fact that geese used in the study were reared under breeder conditions.…”
Section: External Quality Traitscontrasting
confidence: 97%
“…Shape index ratio determined in the present study was similar to the values (64.9% and 67.5%) reported by Mazanowski and Bernacki [19] for White Italian × Slovakian × Graylag geese and those (66.40% and 67.28%) stated by Arslan and Saatci [20] for geese native to the region of Kars. However, Zhang et al [21] found that the shape index was 69% for 2-year-old geese, which was lower than the value found in the present study. This may be associated with breed, origin, and age of the geese and mainly the fact that geese used in the study were reared under breeder conditions.…”
Section: External Quality Traitscontrasting
confidence: 97%
“…The shell was differentiated according to the egg parts and it was observed that there was a thickening from Blunt end to Sharp end as reported previously (Balkan and Biricik 2006, Fiialovych and Kyryliv 2016, Zhang et al 2017. The difference between parts in this study was found to be much A Study on the Effect of Altitude on Shell Thickness in Goose Eggs more distinctive than the earlier studies (p<0.001).…”
Section: Resultssupporting
confidence: 83%
“…The egg shell is not in the same thickness in all areas of the egg and generally shows thickening from blunt to sharp end. In their study on goose eggs, Zhang et al (2017) measured the blunt end as 0.479 mm, equatorial 0.510 mm and the sharp end 0.510 mm. Fiialovych and Kyryliv (2016) found the blunt end as 0.52 and the sharp end as 0.53 mm.…”
Section: Introductionmentioning
confidence: 99%
“…Comparatively, goose eggs present higher breaking strength (74.17-105.32 N); however, they are larger than turkey eggs, with average length of 78.26 mm and width of 53.62 mm (Zhang et al, 2017). Nedomova et al (2014) also reported higher breaking strength in goose eggs (63.80-101.92 N) loaded at the same compression speed of 0.33 mm s -1 as in the present study.…”
Section: Some Physical Morphological and Mechanical Characteristicssupporting
confidence: 51%